A Study of the Kidney of the Wistar Rat in Northern\ Guinea Savannah Zone: The Morphometric Aspect - Onyeanusi, B.I.; Adeniyi, A.A.; Onyeanusi, C.G.; Ayo, J.O.; Ibe, C.S. (Pakistan Journal of Nutrition, 2009)
A morphometric study was carried out on the kidney of the Wistar Rat (WR) using standard laboratory procedures. The mean live weight of the Wistar rat was found to be 140.625±3.078 g. The average kidney weight was 0.605±0.012 g. The right kidney, with a mean weight of 0.632±0.012 g, was significantly (p